Spiritual Development and Commitments to Emancipatory Education in Women Adult Educators for Social Change - Elizabeth J. Tisdell (Adult Education Research Conference, 2000)
This paper discusses the results of a qualitative research study of the spiritual development of a multicultural group of women adult educators for social change, and its relationship to their current commitment to emancipatory adult education practice.